Meniscal Root Repairs. Issue 4 (October 2015) - LaPrade, Robert F.; Moulton, Samuel G.; Cram, Tyler R.; Geeslin, Andrew G.; LaPrade, Christopher M.; Engebretsen, Lars
Abstract : Meniscal root tears are substantial injuries that usually require surgical management. If left untreated, meniscal root tears can lead to the rapid onset of osteoarthritis similar to that seen after a total meniscectomy. Meniscal root tears often go unnoticed on magnetic resonance imaging and arthroscopy, in large part because meniscal root anatomy and its biomechanical importance have been defined only recently. In a transtibial meniscal root repair, the current clinical standard of care, the root is reattached to its native attachment site on the tibial plateau, restoring tibiofemoral contact mechanics. While this video article shows a posterior medial root repair technique, the same anatomic, biomechanical, and surgical principles apply to a posterior lateral meniscal root attachment. The principal steps in this procedure include (1) verifying the presence of a posterior medial meniscal root tear with arthroscopic visualization and probing, (2) inspecting the root tear and debriding the root attachment site to bone with a curet, (3) arthroscopic release of any adhesions that cause retraction of the meniscal root to a nonanatomic position, (4) drilling of two separate transtibial tunnels that extend down to the anteromedial portion of the tibia, (5) placing an accessory portal to pass the sutures, (6) placing two simple sutures through the torn meniscal root and shuttling them down the tibial tunnels, and (7) tying the sutures over a surgical button on the anteroproximal portion of the tibia with the knee flexed 90°. Postoperatively, patients remain non-weight-bearing for six weeks. Passive knee flexion from 0° to 90° is allowed for the first two weeks. After two weeks, motion is increased as tolerated. Patients initiate weight-bearing at postoperative week six and commence the use of a stationary bicycle. Resistive exercises are slowly progressed, and the patient should avoid squatting as well as squatting and lifting for four months. Patients are expected to return to normal physical activity within four to six months postoperatively.